2014
DOI: 10.1007/s00348-013-1662-8
|View full text |Cite
|
Sign up to set email alerts
|

On the formation of string cavitation inside fuel injectors

Abstract: The formation of vortex or 'string' cavitation has been visualised in the flow upstream of the injection hole inlet of an automotive-sized optical diesel fuel injector nozzle operating at pressures up to 2000 bar. Three different nozzle geometries and three-dimensional flow simulations have been employed to describe how, for two adjacent nozzle holes, their relative positions influenced the formation and hole-to-hole interaction of the observed string cavitation vortices. Each hole was shown to contain two cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Reid et al used sapphire plates to create a simplified version of the geometry found in valve-covered-orifice injectors. 9,10 They achieved injection pressures of 2000 bars with the design. The orifice was constructed by stacking sapphire plates with holes of various sizes on top of each other.…”
Section: B Past Studiesmentioning
confidence: 99%
“…Reid et al used sapphire plates to create a simplified version of the geometry found in valve-covered-orifice injectors. 9,10 They achieved injection pressures of 2000 bars with the design. The orifice was constructed by stacking sapphire plates with holes of various sizes on top of each other.…”
Section: B Past Studiesmentioning
confidence: 99%
“…Cavitation in true-scale injectors operating under realistic injection pressures has been also studied, for example see selectively Andriotis et al [24], Giannadakis et al [25], Mitroglou et al [26,27], and Reid et al [28,29]. Out of those, the study from Reid et al [28] has been the only one to visualize cavitation at pressures up to 2050 bars.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that longitudinal vortices detected as string cavitation formed at the axes of the two parallel holes, whereas an additional cavitating vortex of horseshoe shape was found to "bridge" the two holes. In a subsequent study [29] referring to the same nozzle layout, it was pointed out that the secondary flow topology exhibits significant discrepancies in the cases of steady state and transient fuel injection conditions. The significance of this study lies on the fact that the same macroscopic flow features that have been observed in transparent nozzles operating at much lower pressures (from a few bar up to 600bar) are present at pressure levels similar to those in real metallic nozzles.…”
Section: Introductionmentioning
confidence: 99%
“…The results distinguished the formation process of cavitation for two different flow conditions. With a detailed comparison between the vortex string observed in experiments and the flow streamlines of numerical simulation, Reid et al (2014) succeeded in interpreting the origin of the cavitating lobes in a diesel fuel injector. Koukouvinis et al (2017) proposed a similar numerical method, and studied the correlation between the cavitation evolution and turbulence distribution.…”
Section: Introductionmentioning
confidence: 99%